2017
DOI: 10.3906/vet-1609-58
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal barrier and mucosal immunity in broilers, Thai Betong, and native Thai Praduhangdum chickens

Abstract: The intestinal barrier includes physical and chemical components for preventing the invasion of pathogenic and toxic agents. The aim of this study was to investigate small intestinal morphology, antimicrobial peptides, and tight junction (TJ) distribution among broilers, Thai Betong chickens, and native Thai Praduhangdum chickens. Intestinal samples from 40 chickens of each breed were collected. The results of the histological and morphological examination revealed that the duodenum of all breeds had the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Mucin coats the gastrointestinal tract, and it is accepted as the first-line host defense. These cells in the intestinal mucosa provide lubricity via mucin which also acts as a protective barrier against pathogenic microorganisms [ 52 ]. Gao et al [ 46 ] reported that the increase in the GCC may be related to the increase in the CD, which reflects epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Mucin coats the gastrointestinal tract, and it is accepted as the first-line host defense. These cells in the intestinal mucosa provide lubricity via mucin which also acts as a protective barrier against pathogenic microorganisms [ 52 ]. Gao et al [ 46 ] reported that the increase in the GCC may be related to the increase in the CD, which reflects epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin1, Claudin5, and Claudin16 are interstitially located in the intestinal mucosal epithelial cells and together form a tight junction in chickens (Ozden, et al, 2010;Theerawatanasirikul, et al, 2017). In contrast, Claudin5 and JAM2 proteins are not only expressed in the mucosal epithelium, but also in the vascular endothelial cells of mice (Martin-Padura, et al, 1998;Morita, et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells are protected from physical damage by intraluminal substances and block the invasion of pathogenic bacteria. To provide continuous protection, goblet cells must constantly be renewed [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%